Sistem Informasi Pengolahan Data Anak Pada Pusat Pengembangan Anak (PPA) Di Gks Prailangina - Rambu Lemba, Relsia; Rada, Yustina; Albert Agustin Lobo, Murry (Jurnal Manajemen Teknologi Dan Sistem Informasi (JMS), 2025)
Advances in information technology in Indonesia have now spread to various sectors, including in the field of social institutions, as seen in the Indonesian Compassion Foundation. This foundation focuses on Child Development Centers (PPA) and collaborates with churches throughout the world, including those in Indonesia. One of the branches is at the Sumba Christian Church (GKS) Prailangina, namely PPA IO 323 Deo Volente. In one week, they are required to take part in PPA activities three times, namely on Tuesday, Wednesday and Thursday. Recording activities carried out include: learning data, health data and service data. This recording process is still carried out manually by the mentor by recording it in a book, then the mentor hands it over to the coordinator, who then transfers the data into Microsoft Excel to be processed and reported to Compassion as an accountability activity every month. So the problem faced by PPA at GKS Prailangina is inefficiency in processing children's data, which poses a high risk to data security because writing errors and data loss often occur. This causes the data search process to become slow and complicated, as well as delays in processing and producing reports. This research aims to design a website-based children's data processing information system using the waterfall model system development method. The programming language used in developing this system is PHP, with MySQL as the database. The results of this research show that implementing an information system can make it easier for PPA staff to process computerized child data.